Conquering the sky the secret flight of the wright brothers - Tise, Larry E. (Palgrave Macmillan, 2009)
In seven crucial days of spring 1908, the Wright brothers prepared for what they thought would be a season of secret flights at Kitty Hawk, the culmination of five years spent perfecting their planes. However, they were soon discovered by a host of fast-paced reporters and photographers, forcing the brothers to try to outsmart the world press and avoid close scrutiny of their flying machine and its prowess. Within a few pivotal days, the brothers were catapulted into unwanted worldwide fame as the international press reported their every move using rudimentary telegraphs and early forms of photography. This comedy-of-errors pursuit of pilots and press resulted in a series of bizarre and far-fetched news stories splashed across front pages around the world, by journalists who knew they had just witnessed a milestone in history and were desperate to get to the story first. In Conquering the Sky, Larry E. Tise tells the fascinating untold story of how the Wrights finally introduced the world to the power of flight, taught a legion of gaping aeronauts how to put a plane in the air and keep it there, and astonished thousands of eye-witnesses both in America and in Europe with their amazing feats